2018
DOI: 10.1038/s41467-018-06603-5
|View full text |Cite
|
Sign up to set email alerts
|

Cationic nanoparticle as an inhibitor of cell-free DNA-induced inflammation

Abstract: Cell-free DNA (cfDNA) released from damaged or dead cells can activate DNA sensors that exacerbate the pathogenesis of rheumatoid arthritis (RA). Here we show that ~40 nm cationic nanoparticles (cNP) can scavenge cfDNA derived from RA patients and inhibit the activation of primary synovial fluid monocytes and fibroblast-like synoviocytes. Using clinical scoring, micro-CT images, MRI, and histology, we show that intravenous injection of cNP into a CpG-induced mouse model or collagen-induced arthritis rat model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 48 publications
6
115
0
Order By: Relevance
“…Encouraged by the high NA-binding capacity and effective inflammatory inhibition of cNPs in a previous study ( 19 ), we used cNPs to interfere with the cfDNA-LL37 complex for psoriasis treatment. In particular, the excellent NA-binding capability of cNPs by charge interactions resulted in potent destruction of the NA inflammasome by forming a more compact polymer-NA complex.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by the high NA-binding capacity and effective inflammatory inhibition of cNPs in a previous study ( 19 ), we used cNPs to interfere with the cfDNA-LL37 complex for psoriasis treatment. In particular, the excellent NA-binding capability of cNPs by charge interactions resulted in potent destruction of the NA inflammasome by forming a more compact polymer-NA complex.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that nanoparticles can also be exploited for the removal of DAMPs such as cell-free DNA that is expelled from dying cells to ameliorate inflammatory diseases initiated by the inappropriate activation of TLR signaling. Hence, Liang et al 119 prepared cationic nanoparticles composed of the block copolymer of PLGA and poly(2-(diethylamino)ethyl methacrylate), and found that these particles had a high DNA-binding capacity. Furthermore, when injected intravenously the cationic nanoparticles could alleviate symptoms in animal models of arthritis.…”
Section: Decoding Danger At the Nanoscalementioning
confidence: 99%
“…Although the factors that drove persistent cellular activation in RA remain elusive, the data from animal models and clinical studies suggest that cfDNA plays a key role in driving inflammation for RA . By scavenging the cfDNA, recently we showed that polycationic nanoparticles can inhibit the persistent inflammation in RA to achieve significant symptom relief . Here we designed and synthesized a series of cationic dendronized polymers (cDenpols) to demonstrate that toxicity, NA binding capacity, and biodistribution could be balanced to achieve maximum therapeutic effect with exquisite control of the molecular structure.…”
Section: Figurementioning
confidence: 99%